MULTITEMPORAL ANALYSIS OF THE RELATIONSHIP BETWEEN LANDFORMS AND URBAN EXPANSION. CASE STUDY: CLUJ-NAPOCA, ROMANIA - HOSU, Maria; NAN, Flavia-Oana (Studia Universitatis Babeș-Bolyai Geographia, 2025)
Given the current trend of urban development in Cluj-Napoca, the growing demand for land, and the expansion of the built-up area, this study aims to analyze the effects of urban development on landforms, while also establishing their functionality in an urban context. A multitemporal and multidisciplinary approach is essential for understanding the dynamics between relief and urban expansion, combining data from geomorphology, history, and urban planning. Field research is fundamental to this study for observations and direct verification of data. The analysis method exploits the principles of data overlay and spatial analysis using GIS (Geographic Information System). The starting point was the premise that within the urban area, the dynamics of the relief and/or the evolution of the geomorphological landscape are strongly influenced by anthropogenic action. The multidisciplinary integration of data facilitated the recognition and reconstruction of geological and geomorphological characteristics and changes in the function of the relief during urban expansion and the reconfiguration of land use: areas that were previously classified as unsuitable for construction and delimited as extra-urban, used mainly for agriculture, are now revalued as buildable land as a result of pressure from urban expansion. In other words, land is undergoing a process of functional reevaluation, in which the values and roles of landforms are reinterpreted according to the needs of urban development.